Preceramic core-shell particles for the preparation of hybrid colloidal crystal films by melt-shear organization and conversion into porous ceramics. (15th December 2018) - Vowinkel, Steffen; Boehm, Anna; Schäfer, Timmy; Gutmann, Torsten; Ionescu, Emanuel; Gallei, Markus
Abstract: In this work, the preparation of porous hybrid particle-based films by core-shell particle design and convenient film preparation is reported. Monodisperse core particles consisting of poly(methyl methacrylate‑ co ‑allyl methacrylate) (P(MMA‑ co ‑ALMA)) were synthesized by starved-feed emulsion polymerization followed by the introduction of an initiator-containing monomer (inimer) for subsequent atom transfer radical polymerization (ATRP). The inimer shell allowed for the introduction of allylhydrido polycarbosilane (SMP-10) under ATRP conditions by grafting to the core particles. The functionalization of the prepared core-shell particles was investigated by IR spectroscopy (FTIR), scanning transmission electron microscopy (STEM) and solid-state NMR combined with dynamic nuclear polarization (DNP). The obtained hard core/soft preceramic shell particles were subjected to the melt-shear organization technique, enabling a convenient alignment into a colloidal crystal structure in one single step without the presence of a dispersion medium or solvent for the designed particles. Moreover, the hybrid particle-based films were converted into a porous ceramic structure upon thermal treatment. As a result, freestanding ceramic porous films have been obtained after degradation of the organic template core particles. Noteworthy, the conversion of the matrix material consisting of SMP-10 into the ceramic occurred with preservation of the pristine colloidal crystal template structure. Herein, the first example of core-shell particle preparation by combining different polymerization methodologies and application of the convenient melt-shear organization technique is shown, paving a new way to ceramic materials with tailored morphology and porosity. Graphical abstract: Highlights: Preparation of porous hybrid particle-based films by core-shell particle design and conversion to a ceramic material Synthesis of preceramic core-shell particles by a combination of emulsion polymerization and ATRP Processing by melt-shear organization into colloidal crystals films and removal of the particle template by thermal treatment Tailored pore size design of ceramic inverse opals